Online reported women’s experiences of symptomatic pelvic organ prolapse after vaginal birth - Maria Mirskaya (BMC Women's Health, 2019)
Abstract Background Pelvic organ prolapse (POP) is a major public health problem with a relative high lifetime risk of surgery. The main risk factor for developing POP is vaginal birth. Many women become symptomatic later in life and most of the existing research on symptomatic pelvic organ prolapse (sPOP) predominantly concentrates on the effects of the condition on postmenopausal women. However bothersome symptoms of POP can be reported as early as in women’s 20s and may occur shortly after vaginal birth. Limited studies provide an insight into daily life of fertile women with sPOP. Thus, we aimed to explore fertile women’s experiences of symptomatic pelvic organ (sPOP) after vaginal birth. Methods An inductive, text-driven approach was taken by selecting thread posts from an internet forum written by 33 Swedish fertile women who had experienced sPOP after vaginal birth. Results The overarching theme “being irreparably damaged” was identified as representing an experience of being disabled by sPOP after vaginal birth. The fertile women experienced that their lives were ruined because of physical and psychological limitations caused by this unexpected, unfamiliar and unexplained condition. Living with sPOP impinged on sexual health, restricted daily and sports activities and affected the women’s ability to fulfill everyday parental duties. This in turn compromised women’s psychological health. In addition, the negligence of healthcare professionals who tended to trivialize and normalize the symptoms led to the belief that there were no sustainable treatments and that women would have to live with bothersome symptoms of POP for rest of their lives. Conclusions This study found that sPOP had a significant negative impact on fertile women’s lives. The women indicated that they had not had the opportunity to voice their concerns and had not been taken seriously by healthcare professionals. It is of the utmost importance to acknowledge this problem and develop guidelines for prevention and management of sPOP to improve the quality of life for women.